2013
DOI: 10.1126/science.1230082
|View full text |Cite
|
Sign up to set email alerts
|

KNOX2 Genes Regulate the Haploid-to-Diploid Morphological Transition in Land Plants

Abstract: Unlike animals, land plants undergo an alternation of generations, producing multicellular bodies in both haploid (1n: gametophyte) and diploid (2n: sporophyte) generations. Plant body plans in each generation are regulated by distinct developmental programs initiated at either meiosis or fertilization, respectively. In mosses, the haploid gametophyte generation is dominant, whereas in vascular plants-including ferns, gymnosperms, and angiosperms-the diploid sporophyte generation is dominant. Deletion of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
161
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(161 citation statements)
references
References 32 publications
0
161
0
Order By: Relevance
“…Hence, in a developmental comparison of homologous structures between non-vascular and vascular plants, moss gametophytes correspond to flowering plant gametophytes, i.e., the pollen and the embryo sac. At the molecular level, the developmental programs underlying the gametophyte and sporophyte body plans are often not synapomorphies of land plants and rely on different mechanisms (Sakakibara et al 2013).…”
Section: Mosses Are Haploid Dominantmentioning
confidence: 99%
“…Hence, in a developmental comparison of homologous structures between non-vascular and vascular plants, moss gametophytes correspond to flowering plant gametophytes, i.e., the pollen and the embryo sac. At the molecular level, the developmental programs underlying the gametophyte and sporophyte body plans are often not synapomorphies of land plants and rely on different mechanisms (Sakakibara et al 2013).…”
Section: Mosses Are Haploid Dominantmentioning
confidence: 99%
“…Interestingly, the genetic program that directs sporophyte development in the bryophyte moss Physcomitrella is directed by a KNOX family homeodomain transcription factor whose homologs in the chlorophyte alga C. reinhardtii direct development of the dormant diploid zygospore formed after fertilization (Lee et al 2008;Nishimura et al 2012;Sakakibara et al 2013). The role of these homeodomain proteins in charophyte algae has not been examined, but they are predicted to participate in zygote development.…”
Section: Multicellular Innovations In Land Plants That May Be Rootedmentioning
confidence: 99%
“…Recently, Sakakibara et al (2013) demonstrated that inactivation of moss class 2 KNOTTED LIKE HOMEO-BOX (KNOX2) transcription factors induce the development of gametophyte leafy shoots from diploid embryos without meiosis, suggesting that PpKNOX2 acts to prevent the haploid-specific body plan from developing in the diploid phase. This result is intriguing, as it may suggest that loss of such a pathway potentially could have aided in the recruitment of haploid genetic tool kits into the diploid generation.…”
mentioning
confidence: 99%